(untitled) (Publicacions de la Universitat de València, 2019)
This collection of essays by the historian and activist Aviva Chomsky includes work on topics ranging from immigration, to labor history, to popular culture. Chomsky’s incisive prose brings the perspective of a historian to bear on current events in a way that adds depth and nuance to topics that are of the utmost importance at this moment in world history. Unwanted People fits into Chomsky’s larger project to debunk the mythical history of the United States as a nation of immigrants or a melting pot. Her work uncovers centuries of racially motivated immigration policies that inform the current rhetoric surrounding immigration and displaced peoples. Her essays build on that foundation and expand into new territory. Exploring history as a discipline that works from the ground up rather than from the top down, Chomsky challenges the dominant narratives and gives voice to disenfranchised and unwanted people. Touching on topics from revolutionary violence and race to colonialism and its aftermath, this collection of lucid thoughts reveals the hidden histories of the people who shape our modern political and economic landscape. Esta recopilación de ensayos de la historiadora y activista Aviva Chomsky incluye trabajos sobre temas que van desde la inmigración, pasando por la historia laboral, hasta la cultura popular. La prosa incisiva de Chomsky aporta una perspectiva histórica a los acontecimientos actuales de manera que añade profundidad y matices a temas que son de la mayor importancia en este momento de la historia mundial. ‘Unwanted people’ es el proyecto más grande de Chomsky para desacreditar la historia mítica de los Estados Unidos como una nación de inmigrantes o un crisol de razas. Su trabajo revela siglos de políticas de inmigración racialmente motivadas que conforman la retórica actual en torno a la inmigración y las personas desplazadas. La autora desafía las narrativas dominantes y da voz a las personas marginadas y no deseadas. Tocando temas que van desde la violencia revolucionaria y la raza hasta el colonialismo y sus secuelas, esta colección de pensamientos lúcidos revela las historias ocultas de las personas que dan forma a nuestro paisaje político y económico moderno.